Sistem Pemesanan Berbasis Web Pada Usaha Bouquetqu.AD Menggunakan PhP Dan MySQL - Jeni Vegas Tamah; Indra Kanedi; Ricky Zulfiandry (UNIVED Press, 2025)
Advances in information technology have encouraged micro, small, and medium enterprises (MSMEs) to adapt through the digitization of business processes, including ordering systems. The research aims to design and implement a web-based ordering system for Bouquetqu.ad—a creative business in Bengkulu City specializing in the sale of gift bouquets. The system was developed to address the limitations of the manual ordering system previously used, which had resulted in low efficiency and limited marketing reach. The system development method used is Waterfall Model, with stages including needs analysis, system design, implementation, testing, and maintenance. The programming language PHP and MySQL database were chosen as the primary platform due to their open-source nature, flexibility, and suitability for developing web applications at the SME scale. The implementation results show that the developed system can improve the efficiency of the ordering process, expand service reach to customers, and minimize data errors. Testing using the black box method indicates that all functions operate as planned. With this system, Bouquetqu.ad can enhance service quality while boosting competitiveness in the digital era